2022
DOI: 10.1002/anie.202213653
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Benzylic C(sp3)−H Functionalizations: Divergent Synthesis of Indole[a]‐ and [b]‐Fused Polycycles**

Abstract: Phenyl azidessubstituted by an (alkylphenyl)ethynyl group facilitate benzylic sp 3 (CÀ H) functionalization in the presence of a JohnPhosAu catalyst, resulting in indole-fused tetra-and pentacycles via divergent N-or C-cyclization. The chemoselectivity is influenced depending on the counter-anion, the electron density of the α-imino gold(I) carbene, and the alkyl groups stabilizing the benzylic carbocation originating from a 1,5-hydride shift. An isotopic labeling experiment demonstrates the involvement of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…With the support of the above experimental results and previous achievements on the generation of α-imino metal carbenes from cyclization of azide–ynamides, , a possible mechanism for the construction of azepino­[2,3- b :4,5- b ′]­diindoles is presented in Scheme . Taking substrate 1a for example, phenyl azide as a nucleophile could initially attack the copper-activated triple bond in 1A to form vinylcopper species 1B , which could smoothly generate α-imino copper carbene intermediate 1C by the release of N 2 .…”
supporting
confidence: 68%
See 1 more Smart Citation
“…With the support of the above experimental results and previous achievements on the generation of α-imino metal carbenes from cyclization of azide–ynamides, , a possible mechanism for the construction of azepino­[2,3- b :4,5- b ′]­diindoles is presented in Scheme . Taking substrate 1a for example, phenyl azide as a nucleophile could initially attack the copper-activated triple bond in 1A to form vinylcopper species 1B , which could smoothly generate α-imino copper carbene intermediate 1C by the release of N 2 .…”
supporting
confidence: 68%
“…The first example of the generation of α-imino gold carbenes via gold-catalyzed azide–alkyne cyclization was developed in 2005 by Toste and co-workers . Under the continuous and in-depth exploration by Zhang, Gagosz, Ohno, Ye, and others over the past decades, this strategy of gold-catalyzed tandem cyclization has become a versatile platform for the synthesis of diverse useful N-heterocycles. Very recently, Gagosz and Ohno demonstrated a very similar methods for synthesizing indole derivatives through gold-catalyzed C­(sp 3 )–H functionalization originating from azide–alkynes.…”
mentioning
confidence: 99%
“…In our previous work, we reported that hydride migration on α-imino gold carbenes is practical for generating polycyclic indoles 11 (Scheme 3). [30][31][32] Based on extensive research by Gagosz [33][34][35] and Davies, [36] introducing the oxygen functional group facilitates hydride transfer to electrophilic alkynyl gold complexes. Accordingly, we attempted to enhance the hydride transfer step on gold carbenes, via introducing an alkoxy group at the benzylic position, by stabilizing the benzylic cation species H (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%
“…This has mainly been achieved either by intercepting α-imino gold carbenes by an array of nucleophiles including hydrides/alkyls (via 1,2-migration), arenes and heteroarenes, alcohols, alkenes, amines (via 1,2-migration), etc. ; or by various annulation and carbene metathesis reactions (Scheme b). As a result, the topic has now culminated in an important and vast branch of gold carbene chemistry and has recently been reviewed comprehensively …”
mentioning
confidence: 99%
“…Notably, pseudanes have been rigorously investigated for their biological properties, including antimicrobial, antiplasmodial, anti-inflammatory, antimelanogenic, quorum sensing, and anti-MRSA activities and have attracted the attention of many organic chemists. , Pseudanes being a vast family of natural products, as representative examples, we have realized the synthesis of four C 3 -fluorinated analogues, namely, pseudane III ( 2s ), pseudane VI ( 2t ), pseudane VII ( 2u ), and pseudane VIII ( 2v ) in 56–62% yields (Scheme ). Apart from quinolones, the synthesis of indoles and similar fused aza-heterocycles has been explored by using various 1-azido-2-(aryl/alkylethynyl)­benzene-based cores. ,,− ,,,,,,, To our delight, with some modifications to the optimized reaction conditions, this fluorination technique could also be applied for the synthesis of C 3 -fluorinated indoles, as well. As depicted in Scheme , both aryl (−Ph) and alkyl substituents (− n Hex) at alkynes were tolerated well to afford the corresponding C 3 -fluorinated indoles 5a and 5b in 60% and 49% yields, respectively.…”
mentioning
confidence: 99%